THE EFFECT OF REFORMS IMPLEMENTED IN THE REPUBLIC OF UZBEKISTAN (Proceedings of International Educators Conference, 2023)
It is difficult for us to imagine our life without water, because the main part of our existence depends on water. Water is the most important source of life for every living thing on earth. That is why our nation has always paid serious attention to the wise use of water resources and its preservation.